2003
DOI: 10.1002/cvde.200290002
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Epitaxial and Polycrystalline SnO2 Films from the SnI4/O2 Precursor Combination

Abstract: Thin films of SnO 2 have been successfully deposited by atomic layer deposition (ALD) using the SnI 4 /O 2 precursor combination. Depositions were carried out in the temperature range 400±750 C on SiO 2 /Si(100) and single-crystalline a-Al 2 O 3 (012) substrates. The films were found to grow as the tetragonal SnO 2 phase (cassiterite), polycrystalline on SiO 2 /Si (100)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…The deposition experiments were performed in a reactor designed for ALD, which has been described in more detail elsewhere [25]. The ALD reactor was operated in CVD mode by feeding in the precursors simultaneously.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The deposition experiments were performed in a reactor designed for ALD, which has been described in more detail elsewhere [25]. The ALD reactor was operated in CVD mode by feeding in the precursors simultaneously.…”
Section: Methodsmentioning
confidence: 99%
“…A reason why the 180 twin often has a reduced intensity compared to the main orientation has earlier been proposed in the case of ALD of SnO 2 . [25] It might be due to the fact that the oxygen atoms are not superimposed in the contact plane between the a-Al 2 O 3 (012) and SnO 2 (101) planes (see Fig. 9a,b) and hence is not as energetically favorable.…”
Section: Epitaxial Relationshipsmentioning
confidence: 98%
See 1 more Smart Citation
“…All films were deposited in an on-site-built, hot-wall, horizontal flow-type ALD reactor that has been described in detail elsewhere [28]. The reactor consists of a 40 mm main quartz tube with two smaller quartz tubes, 20 mm and 25 mm, inserted inside.…”
Section: Methodsmentioning
confidence: 99%
“…However, Ta 2 O 5 has previously been deposited by CVD using the TaI 5 /O 2 precursor combination. [15] Furthermore, it has been shown that it is possible to grow other metal oxides by ALD from metal iodides in combination with O 2 , for example TiO 2 , [16] SnO 2 , [17] and HfO 2 . [18] Very low levels of iodine contamination were reported when the metal iodides were employed, whereas when chloride precursors were used, significantly higher levels of chlorine contamination have been observed.…”
Section: Introductionmentioning
confidence: 98%